Improving The Pronunciation Ability Of Class X Pplg 1 Students Through Google Translate Voice In Descriptive Text Learning (psnppg, 2023)
This research aims to improve the students from X PPLG 1 SMK Negeri 2 Semarang ability in pronunciation by using google translate voice. The researchers focus on the student problems that can be improved through the application of technology to the descriptive text learning process. This research was carried out in 2 cycles and in each cycle there were activities such as planning, implementation, observation and reflection. This type of research is Classroom Action Research  which uses qualitative and quantitative methods. To obtain the results or data, researchers use data collection techniques, such as observations, tests, field notes and documents that function as recorders of student pronunciation in the classroom. The results of the data from this research show that students in the pre-test got an average score of 47.11, then in the post-test cycle I students got an average score of 61.11 and in the post-test cycle II students got an average score of 80. 00. Based on the result of the data, shows that research on the application of Google Translate Voice to improve students' pronunciation skills was successful and experienced improvement in each implementation, starting from pre-test to post-test cycle I and from post-test cycle I to post-test cycle II.
Keywords: The ability of pronunciation; Google translate voice; Descriptive text